GYNOGENESIS INDUCTION IN CULTURE OF UNPOLLINATED OVULES OF PUMPKIN - N.A. Shmykova; D.V. Shumilina; V.P. Kushnereva; G.A. Khimich (Овощи России)
The perspective of utilization of in vitro culture of unpollinated ovules for development of dihaploid lines of pumpkin is described in the article. The ovules of five hybrids were cultivated on CBM medium. The following combinations of growth regulators for gynogenesis induction were used: a) 0.2 mg/L of thidiazuron and 0,0001 мкМ of epibrassinolide; b) 2 mg/l of 2,4-D. The frequency of embryo development depended on cultivation medium and genotype. The maximum amount of embryos developed from unpollinated ovules of one ovary was 6-9 ones.